Government connections and credit access around the world: Evidence from discouraged borrowers - Qi, Shusen; Nguyen, Duc Duy (Journal of International Business Studies, 2021)
Motivated by the international business literature that examines the interactions between organizations, corruption, and political forces, we examine whether and how government connections affect small and medium-sized enterprises’ (SMEs) credit access around the world. Using a sample of SMEs across 30 developing countries, we show that SMEs with government connections are significantly less likely to be discouraged from approaching banks for a loan as compared to SMEs without such connections. However, connected SMEs do not receive preferential lending from banks. Moreover, the nature of this effect depends on the institutional setting. Specifically, the effect becomes stronger in countries with high levels of corruption, suggesting that government connections are substitutes for poorly functioning formal institutions. Our findings have important implications for policies targeted at reducing corruption, improving access to financing, facilitating entrepreneurship, and attracting foreign investment.